Mathematics: The Loss of Certainty by Morris Kline - Aickin, Mikel (Journal of Scientific Exploration, 2012)
In 1980 Morris Kline wrote this engaging book, in which he took on many of the myths about the nature and history of mathematics. This new edition will probably be as seldom read as the original, which is too bad because it contains important messages, including perhaps some comfort for anomalies researchers. I will briefly present an overview of the book’s contents, and then say what I think these comforts are. · · · The ancient Greeks developed the seed of what we now think of as mathematics. Kline points out that their mathematical concepts arose from consideration of the natural world, and then the fact that numbers, shapes, and relationships corresponded to things in the real world convinced them that reality itself was in some mystical way generated by numerical principles. The regular patterns that they found in geometric forms and simple integers reflected the regularities of nature, and so provided keys to understanding how things were, and why they were that way. The faith that mathematics lay behind the mundane world of observations became an unquestioned truth, at least as important as the practical techniques the Greeks devised, and passed along through the Middle East and the medieval period to modern Europe.